The Influence of Glass Fiber and Milled Glass Fiber on the Performance of Iraqi Oil Well Cement - Assi, Amel Habeeb; Almahdawi, Faleh H. M.; Khalti, Qasim Abdulridha (Journal of Petroleum Research and Studies, 2021)
The reinforced fiberglass in cement slurry reflects the effect on its properties compared to usual additives. Fiberglass is typically used in cement slurry design for one or another of the following goals: (Earth earthquake, bearing storage, and with differential stresses, to enhance cement durability and increase its compressive strength). The main goal is to use glass fiber and ground fiberglass to improve the tensile strength and moderate compressive strength significantly. On the other hand, the use of glass fibers led to a slight increase in the value of thickening time, which is a desirable effect. Eleven glass fiber samples and milled glass fiber were used to show these materials' effect on Iraqi cement with (0.125, 0.25, 0.5, 0.75, 1, and 2) % of cement weight. Those tests used to study cement slurry‟s following properties were compressive strength, thickening time, rheology properties of free water, filtering, and density. These evaluations showed that slurries with less than 1% fiber content gave a higher compressive strength than a sample containing more than 1% glass fiber. However, the slurry mixed with equal or less than 1% milled glass fiber is higher compressive than the sample mixed with more than 1% milled glass fiber. So the optimal concentration for glass fiber is less than 1% by weight of cement (BWOC); either for milled glass fiber, it is less or equal to 1% BWOC. Both materials contributed to increasing the compressive strength of the cement. However, attention must be paid to the ideal This work is licensed under a Creative Commons Attribution 4.0 International License. concentration that should be added during the cement slurry preparation because if we use these two materials carelessly for the ideal concentration, this leads to the collapse and bombardment of the resistance of the cement rock. In other words, the collapse of cement resistance and causing problems during the cementing process.